Pengembangan Skala Thurstone Metode Equal Appearing Interval untuk Mengukur Sikap Moderasi Beragama Siswa Sekolah Menengah Atas - Pratama, Dinar (Jurnal Psikologi Teori dan Terapan, 2020)
Several studies show the increase of radical attitudes among high school students in several regions in Indonesia. Developing a reliable instrument to measure religious moderation attitude is needed as a preventive effort to tackle this trend. However, a standard scale to measure the attitude in the context of Indonesia is extremely rare. This study aims to develop a Thusrtone scale of religious moderation attitude with the Equal Appearing Interval (EAI) method. There were 77 initial items constructed. Forty-two panelists from various relevant backgrounds were involved to assess the initial items. A number of 43 items was selected using the values of median (>6) and interquartile (≤4). The validity of the scale was tested using biserial correlation resulting 42 valid items and 1 invalid item. The result of reliability test using KR 20 technique showed that the scale is strongly reliable with a coefficient value of 0.98. The distribution of scale values on the 42 items of the selected statement lies on a scale value ranging from 1-11. Thus, the scale of religious moderation attitude has fulfilled the psychometric criteria as a measurement scale and can be used to measure students' religious moderation attitudes.Keywords: Thurstone scale, equal-appearing interval method, religious moderation. Abstrak: Beberapa hasil studi menunjukkan tingginya sikap radikal pada siswa Sekolah Menengah Atas (SMA) di beberapa daerah di Indonesia. Mempertimbangkan fenomena ini, diperlukan upaya preventif untuk mengatasi sikap radikal siswa. Salah satu upaya tersebut adalah dengan mengembangkan instrumen yang reliabel untuk mengukur sikap moderasi beragama. Pertimbangan mengembangkan skala ini dikarenakan belum tersedianya skala baku untuk mengukur sikap moderasi beragama siswa. Jenis skala yang dikembangkan adalah skala Thusrtone metode Equal Appearing Interval (EAI) Jumlah aitem awal pada skala ini disiapkan sebanyak 77 aitem. Panelis yang dilibatkan unuk menilai aitem awal sebanyak 42 orang. Analisis pemilihan aitem menggunakan nilai median dan interkuartil menghasilkan 43 aitem terpilih dengan nilai median >6 dan interkuartil ≤4. Pengujian validitas skala dengan  korelasi biserial menghasilkan 42 aitem valid dan 1 aitem tidak valid. Sedangkan uji reliabilitas menggunakan teknik KR 20 menghasilkan nilai koefesien 0.98 yang berarti sangat reliable. Distribusi nilai 42 aitem terpilih terentang dari 1-11. Skala sikap moderasi beragama ini terbukti memenuhi kriteria psikometrik sebagai skala pengukuran dan dapat digunakan untuk mengukur sikap moderasi beragama siswa.